Proposition of Thin-Layer Repairing Methods Using Low-Elasticity Polymer Portland Cement Materials and Glue and Study on the Fatigue Resistance of Reinforced Concrete Slab - Tadashi Abe; Kiyoshi Ito; Noriyuki Kozakai; Takayoshi Kodama (International Journal of Polymer Science)
In this repair method, two types of adhesives, such as a penetrable adhesive and a high-durability adhesive, were applied to the adhesion interface of the materials to be repaired, and then cast. The repair method was then evaluated for fatigue resistance using wheel load running tests. It was developed to ensure the long-term integrity of the repair material and RC slabs. The results of the experiments confirmed that this repair method provides significantly better fatigue resistance than the conventional construction method. Moreover, this study proposes two wet repair cycles and one dry repair cycle with reinforcement measures to improve the load-bearing performance.